The gynecologist, the shepherd of the storks - Palacios Celi, Miguel (2017)
Mr Editor. In the year 1504, when Michelangelo Buonarotti was barely 30 years old, Michelangelo Buonarotti presented the highest summit of all time and today is a world heritage site, The David, sculpted in marble, 4.1 meters high, beautiful on all sides, currently displayed in the Galleria dell 'Accademia in Florence. The artist received praise from kings, princes and connoisseurs, he only needs to speak! they told him. But with great humility he replied by saying that the best of his works compares nothing to a woman giving birth, which is a true work of living art, unique and extraordinary in all times. And so this multifaceted artist showed his respect and admiration for that moment of life, full of mysteries and esotericism, full of fears and superstitions, full of legends and metaphors.